Alcohol consumption among university students in ASEAN countries: A systematic review and meta-analysis - Mayank Kejriwal (Cambridge Prisms: Global Mental Health, 2025)
Alcohol consumption among university students poses significant public health challenges, especially in the Association of Southeast Asian Nations (ASEAN) region, where limited research exists. This review aims to synthesize evidence on sociodemographic factors associated with alcohol consumption among university students in ASEAN countries, assess the study quality and identify research gaps. A systematic search across nine databases was conducted in May 2024, using Population, Intervention, Comparator, Outcome, Study Design and Timeframe to define the inclusion criteria. Studies were assessed for quality and risk of bias using the AXIS tool. Data on sociodemographic factors were extracted, and random-effects meta-analyses were performed for frequently reported factors. Heterogeneity was measured using Cochran’s Q-test and I-squared statistic, and small-study bias was tested using funnel plots and Egger’s test. Fifteen cross-sectional studies involving 35,527 participants met the inclusion criteria. Gender, age and parental alcohol consumption were the most commonly studied factors. Male students had three times the odds of consuming alcohol compared to female students, a result robust to sensitivity analysis. Parental alcohol use and older age were also significantly and positively associated with alcohol consumption, with minimal heterogeneity. Most studies were of high quality, although variability in study design and geographic representation limited the generalizability of the findings. Sociodemographic factors such as gender, age and parental alcohol consumption influence alcohol use among ASEAN college students. However, cross-sectional design and limited country representation highlight the need for further robust research to inform policy and interventions.